2020
DOI: 10.3390/cancers12061671
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Radiosensitive Juvenile Mice by Ultra-High Dose Rate FLASH Irradiation

Abstract: Major advances in high precision treatment delivery and imaging have greatly improved the tolerance of radiotherapy (RT); however, the selective sparing of normal tissue and the reduction of neurocognitive side effects from radiation-induced toxicities remain significant problems for pediatric patients with brain tumors. While the overall survival of pediatric patients afflicted with medulloblastoma (MB), the most common type primary brain cancer in children, remains high (≥80%), lifelong neurotoxic side-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 73 publications
3
90
0
Order By: Relevance
“…Recent data investigating the neurocognitive development of juvenile (3-week old) mice showed a radioprotective FLASH effect following 8 Gy whole brain irradiation with ultra-high FLASH dose rates (4.4 × 10 6 Gy/s, 6 MeV electrons) when compared to conventional dose rates (0.077 Gy/s, 6 MeV electrons) [22]. Mice were subjected to several neurocognitive tests following irradiation and in all cases the performance of the FLASH-irradiated animals was indistinguishable from the control group, whereas conventional irradiation caused a significant detriment.…”
Section: Normal Tissue Sparingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data investigating the neurocognitive development of juvenile (3-week old) mice showed a radioprotective FLASH effect following 8 Gy whole brain irradiation with ultra-high FLASH dose rates (4.4 × 10 6 Gy/s, 6 MeV electrons) when compared to conventional dose rates (0.077 Gy/s, 6 MeV electrons) [22]. Mice were subjected to several neurocognitive tests following irradiation and in all cases the performance of the FLASH-irradiated animals was indistinguishable from the control group, whereas conventional irradiation caused a significant detriment.…”
Section: Normal Tissue Sparingmentioning
confidence: 99%
“…It was suggested that the neurocognitive benefits of FLASH irradiation was due to a preservation of the neurogenic niche and neurogenesis in the FLASH treated mice, with conventional dose-rate-irradiated mice showing considerably lower levels of immature and mature neurons four months post-irradiation. Furthermore, the long-term benefits of FLASH on pituitary function was also investigated and it was found that 8 Gy conventional dose-rate-irradiated mice had a two-fold reduction in levels of plasma growth hormone levels one-week post-treatment compared to the non-irradiated controls, whereas no significant decrease was observed in the FLASH-irradiated animals [22]. Aside from mice, the FLASH effect has also been confirmed in mini-pigs and cats, higher animal models that are more similar to humans [14].…”
Section: Normal Tissue Sparingmentioning
confidence: 99%
“…A recent study by Alaghband et al [ 49 ] investigated the potential for FLASH therapy to preserve the function compared to conventional radiotherapy for the whole brain irradiation of juvenile mice. A whole brain dose of 8 Gy was delivered at a dose rate of 0.077 Gy/s for conventional radiotherapy and 4.4 × 10 6 Gy/s for FLASH radiotherapy.…”
Section: Experimental Medicine In Flash Radiotherapymentioning
confidence: 99%
“…A first clinical application has been reported ( 6 ) and new clinical trials are being approved. Furthermore the potential use of FLASH in pediatrics (e.g., in medulloblastoma) has been cited from studies in juvenile mice ( 27 ).…”
Section: Biology: Revisiting Radiation Biology To Improve Healthy Tismentioning
confidence: 99%